2009
DOI: 10.5005/jp-journals-10006-1037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinicosocial Factors Associated with Antepartum and Intrapartum Stillbirths at Kathmandu Medical College Teaching Hospital

Abstract: Objective To assess the prevalence and biosocial and obstetric risk factors for antepartum and intrapartum stillbirths at a tertiary hospital in Kathmandu, Nepal. Study Design A prospective hospital based study during a one year period from 1st November 2007 to 30th October 2008. Results:18 stillbirths occurred out of the 790 deliveries that took place during the study period giving an overall stillbirth rate of 22.7 per 1000 births of which 22.2% occurred in the intrapartum period. The majority(89.9%) of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[4] The stillbirth rate is a reflection of health status and policies, socioeconomic indicators related to health and access and adequacy of health care. [15]…”
Section: Introductionmentioning
confidence: 99%
“…[4] The stillbirth rate is a reflection of health status and policies, socioeconomic indicators related to health and access and adequacy of health care. [15]…”
Section: Introductionmentioning
confidence: 99%
“…In this study, maximum stillbirths (76%) were in antepartum period compared to 24 percent in intrapartum period compared to 78 antepartum and 22 intrapartum in Rayamajhi et al study, 61% antepartum and 39% intrapartum stillbirths in Vidyadhar study. 3,4 Prasanna et al study observed 72.82% antepartum stillbirths and 21.18% intrapartum stillbirths. 5 In our study antepartum stillbirths in gestational age of 36-40 weeks was 42.8% compared to 42% in Shaaban et al study.…”
Section: Antepartum or Intrapartum Stillbirthmentioning
confidence: 95%
“…This finding was similar to Rayamajhi et al study, with 27.8% stillbirths observed in birth weight range of 2000 to 2500 gm and overall low birth weight babies accounted for 66.6%. 3 According to Vidhyadar et al study, low birth weight and prematurity were responsible for 80% of stillbirths. 4 Birth weight of stillbirth may not be accurate and may be influenced by number of days since fetal death.…”
Section: Stillbirth By Birth Weightmentioning
confidence: 99%